Pengaruh Preferensi Konsumen dan Iklan Online terhadap Keputusan Pembelian pada Produk Skin Hero (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis di Universitas Pembangunan “Veteran” Jawa Timur) - Komang Suparyawan; Rizky Dermawan (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this assessment is to determine impact. from consumer preferences and online advertising to purchase decisions. Hero skin products in mobile legends online games where this should be a tertiary need that does not have to be met first. However, many young people are more concerned with buying skin products than other long-term needs. The population in this study were Management students at the East Java "Veteran" National Development University with a total sample of 101 respondents. This study used a data collection method with a questionnaire distribution system using Google Form media and using Smart PLS as a data analysis tool. The results of this study show that (1) consumer preferences contribute to purchasing decisions for skin hero products and this contribution has a significant impact, (2) online advertising contributes to purchasing decisions for skin hero products and the contributions made have a significant impact.